ANALISIS KEAKTIFAN SISWA SEKOLAH DASAR DENGAN MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN IPA - Nisa Aqidatul Fithri; Ishmatun Naila; Kunti Dian Ayu Afiani (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to analyze the activity of elementary school students using the Project Based Learning model in learning science in Class IV MI Muhammadiyah 6 Sekapuk. The type of research used in this research is qualitative research with a descriptive approach. The research was conducted at MI Muhammadiyah 6 Sekapuk. The subjects in this study were 3 grade IV students. Data collection techniques in this study using data triangulation. The data analysis technique used is qualitative data analysis techniques which include data collection, data reduction, data presentation, and drawing conclusions. The results of the research and discussion obtained by the researcher show that when the teacher applies the Project Based Learning model, the activity of the students increases because they like the existence of the project learning model, which makes them more active and do not tend to be silent during learning. Student K has fulfilled 3 of the 7 indicators of student activity, Student I has fulfilled 4 of the 7 indicators of student activity, and Student A has fulfilled 6 of the 7 indicators of student activity. Of the 7 indicators of student activity, the indicator for student participation in the implementation of learning tasks is the indicator that is most mastered by students.